The Effect of a Combined Modified Pectoral and Stellate Ganglion Block on Stress and Inflammatory Response in Patients Undergoing Modified Radical Mastectomy. (6th June 2022) - Geng, Jun; Wang, Jing; Zhang, Yaowen; Song, Wenxiang; Zhu, Junjia; Chen, Jianqing; Wu, Zhen
Abstract : Background and Aims . Regional anaesthesia reports to attenuate stress and inflammatory responses associated with surgical resection; however, the effectiveness of combined nerve blocks is less often investigated. We evaluated whether a combination of a pectoral nerve block (PNB) and stellate ganglion block (SGB) is more effective than a PNB alone in reducing these responses in women undergoing modified radical mastectomy (MRM). Methods . This is a prospective randomized controlled trial. Fifty patients with breast cancer were randomly allocated to receive an ultrasound-guided PNB (n = 25, PNB only group) or ultrasound-guided PNB combined with SGB (n = 25, combined blockade group). The primary outcome was perioperative plasma level of interleukin- (IL-) 6. Secondary outcomes included perioperative plasma levels of cortisol, glucose, IL-8, and tumour necrosis factor- (TNF-) α, pain scores, haemodynamic variables, sleep quality, and complications postsurgery. Results . The combined blockade group exhibited significantly lower IL-6 and TNF- α levels 24 h postsurgery. Cortisol levels were significantly lower in the combined blockade group at the end of the surgery. Glucose levels at the time of incision were lower in the combined blockade group. Pain scores up to 12 h postsurgery were significantly lower in the combined blockade group, which also exhibited better perioperative haemodynamic stability. Patients in the combined blockade group reported better sleep quality on the night of surgery. Conclusion . In patients undergoing MRM, PNB combined with SGB block effectively blunted perioperative inflammatory response than PNB alone. A combined block approach can also alleviate stress response and postoperative acute pain with stable perioperative haemodynamics and better postoperative sleep quality.